1984
DOI: 10.1002/aja.1001710303
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fiber type composition of the rat hindlimb

Abstract: The purpose of this study was to estimate the absolute and relative masses of the three types of skeletal muscle fibers in the total hindlimb of the male Sprague-Dawley rat (Rattus norvegicus). For six rats, total body mass was recorded and the following weights taken from dissection of one hindlimb: 32 individual major muscles or muscle parts, remaining skeletal musculature (small hip muscles and intrinsic foot muscles), bone, inguinal fat pad, and skin. The fibers from the 32 muscles or muscle parts (which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
515
3
10

Year Published

1996
1996
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 930 publications
(569 citation statements)
references
References 34 publications
41
515
3
10
Order By: Relevance
“…The results showed a predominance of type IIB fibers in the periphery of the fascicles, and of types I and IIA in the more central parts, which also agrees with studies of other mammals (James, 1971a(James, , b, 1972Ariano et al, 1973;Armstrong, 1980;Lexell et al, 1983;Armstrong and Phelps, 1984;Sjøstrøm et al, 1986Sjøstrøm et al, , 1992Hansen et al, 1987;Newsholme et al, 1988;Grotmol et al, 1988;Pernus and Erzen, 1991;Strøm and Holm, 1994). In the present study, type IIB fibers were identified by traditional myosin ATPase histochemistry.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed a predominance of type IIB fibers in the periphery of the fascicles, and of types I and IIA in the more central parts, which also agrees with studies of other mammals (James, 1971a(James, , b, 1972Ariano et al, 1973;Armstrong, 1980;Lexell et al, 1983;Armstrong and Phelps, 1984;Sjøstrøm et al, 1986Sjøstrøm et al, , 1992Hansen et al, 1987;Newsholme et al, 1988;Grotmol et al, 1988;Pernus and Erzen, 1991;Strøm and Holm, 1994). In the present study, type IIB fibers were identified by traditional myosin ATPase histochemistry.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, the soleus muscle is composed of >90% type I fibers, whereas the semimembranosus is composed of >90% type IIB fibers (Armstrong and Phelps, 1984). We used 3-nitrotyrosine (3-NT) as a stable marker of protein oxidative damage.…”
Section: Nitration and Aging Skeletal Musclementioning
confidence: 99%
“…In addition, the surgical preparation does not require removal of facial or cranial bones, which has been the usual protocol for indirect (nerve) extraocular muscle stimulation experiments conducted in mammals (Bach-yRita and Ito, 1966;Barmack et al, 1971;Hanson and Lennerstrand, 1977;Shall and Goldberg, 1992;Dimitrova et al, 2002). For a limb skeletal muscle, the lateral gastrocnemius was selected because it is composed largely of fast muscle fiber types (Armstrong and Phelps, 1984), which is similar to the high percent of fast muscle fiber types found in extraocular muscle. The lateral gastrocnemius muscle can be easily stimulated in situ with wire electrodes in contact with the lateral tibial nerve and has been used frequently for in situ contractile studies (Ameredes and Provenzano, 1997;Grassi et al, 2002;de Haan, 1998;Ma et al, 2004).…”
Section: Surgical Preparation Of Animalsmentioning
confidence: 99%